2016
DOI: 10.1055/s-0042-115416
|View full text |Cite
|
Sign up to set email alerts
|

Microwave Ablation of Symptomatic Benign Thyroid Nodules: Energy Requirement per ml Volume Reduction

Abstract: Zusammenfassung ▼Hintergrund: Mikrowellenablationen (MWA) stellen eine neuartige thermoablative Behandlung für benigne Schilddrüsenknoten dar. Ziel war es, die benötigte Energie pro ml Volumenreduktion zu benutzen, um die benötigte Energie für ein volume-of-interest (VOI) abschätzen zu können. Methode: 25 Patienten mit 25 Knoten (6 solide, 13 komplex und 6 zystisch) wurden durch MWA behandelt. Die übertragene Energie (E) wurde mit der Volumenveränderung (Δ V) nach 3 Monaten korreliert. Der Energiebedarf pro ml… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0
4

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 18 publications
1
4
0
4
Order By: Relevance
“…However, Wang et al [ 30 ] indicated that initial volume, vascularity, and the energy per 1 mL reduction in nodular volume were all risk factors for recurrence of benign thyroid nodules treated with ultrasound guided microwave ablation. In addition, Korkusuz et al [ 31 ] revealed that solid nodules require more the energy per 1 mL reduction than cystic and mixed nodules. Therefore, for large volume nodules requiring high power and long time ablation in clinical practice, they are often prone to recurrence.…”
Section: Discussionmentioning
confidence: 99%
“…However, Wang et al [ 30 ] indicated that initial volume, vascularity, and the energy per 1 mL reduction in nodular volume were all risk factors for recurrence of benign thyroid nodules treated with ultrasound guided microwave ablation. In addition, Korkusuz et al [ 31 ] revealed that solid nodules require more the energy per 1 mL reduction than cystic and mixed nodules. Therefore, for large volume nodules requiring high power and long time ablation in clinical practice, they are often prone to recurrence.…”
Section: Discussionmentioning
confidence: 99%
“…Of late, microwave ablation has been increasingly used for treatment of benign thyroid nodules with satisfactory outcomes [13,14]. Microwave ablation has its own advantages especially with respect to simplified operation and cosmetic benefits; however, it is not suitable for treatment of larger nodules (diameter >30-40 mm) [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…To avoid the occurrence of severe hemorrhage, vessels that are found along the approach route are carefully evaluated using Doppler US (24). Before ablation, local anesthesia with 1% lidocaine is typically injected at the subcutaneous puncture site and the periphery of thyroid nodules to reduce the pain during the skin incision and insertion of an electrode; in instances where cystic components are present, fluid is aspirated before USguided percutaneous ablation (23,(25)(26)(27).…”
Section: Ultrasound-guided Thermal Ablation Techniques and Recent Progressmentioning
confidence: 99%